The Effect of Using Picture Stories on Students’ Reading Comprehension in Narrative Text at the Ninth Grade Students of SMP Negeri 10 Pematangsiantar - Simangunsong, Tiara Indah Sari; Manihuruk, Leonita Maria Efipanias; Hutabarat, Novra Melisa P. (International Journal Corner of Educational Research, 2024)
This research aims to determine whether the use of picture books has a big impact on students' ability to read narrative texts. At SMP Negeri 10 Pematangsiantar, researchers conducted this research using quantitative methods and a quasi-experimental design approach. The population of this study was 201 class IX students. The instruments used to collect data are based on students’ pre-and post-test results. Based on research findings, the average score of the experimental class on the pre-test and post-test was 54 and 75, respectively. The average score of the control group was 58.65 on the pre-test and 65.57 on the post-test as well. The t-test results show (3.7 > 1.677) that the t-test value is greater than the t-table value. H0, the null hypothesis, is refuted. Keeping this in mind, it can be said that picture books play a major role in helping students improve their reading skills, especially in narrative texts.